The Icon of Jesus in the Synagogue in Tiberias and the Polemic Struggle over Appropriation of the Galilee in Late Antiquity - Dvir, Hagay (Vigiliae Christianae, 2026)
The processes shaping the beliefs and ideologies of Galilean inhabitants during Late Antiquity include elements of rewriting traditions and appropriating myths as part of the Jewish-Christian polemical battle. In this article, I start by examining a Christian tradition from Late Antiquity that reconstructs episodes and images from the evangelical narrative, particularly the Passion of Jesus. Significantly, the tradition relocates the narrative from Jerusalem to its Jewish successor in Late Antiquity - Tiberias - the seat of Jewish leadership in the Galilee. This tradition emphasizes the power of icons and their ability to triumph over the Jews and thwart their schemes, in the very heart of their community and in their capital. Using this Christian tradition as a point of departure, I will outline several additional themes, which have parallels in Christian and Jewish literature and then assess the contribution of these themes to better understanding the religious ideological struggle in the Galilee during Late Antiquity.